The effect of ß-receptor blockade on factor VIII levels and thrombin generation in patients with venous thromboembolism - Schönauer, Verena; Giannini, Sandra; Christ, Günter; Quehenberger, Peter; Bieglmayer, Christian; Stain, Milena; Kyrle, Paul A.; Weltermann, Ansgar (Thrombosis and Haemostasis, 2003)
High factor VIII (FVIII) is a risk factor for venous thromboembolism (VTE). The pathomechanism by which high FVIII leads to an increased risk of VTE is unknown. Physical activity and infusion of adrenalin provoke a rise in FVIII, which can be blocked by a nonselective β-blockade. We tested the hypothesis that in patients with a VTE β-blockade decreases FVIII and inhibits coagulation activation.17 male patients with high FVIII (> 170 IU/dL, n = 7) or low FVIII (<150 IU/dL, n = 10) and a history of VTE received 40 mg of propranolol thrice daily for 14 days. FVIII and vasopressin levels were measured before and during propranolol intake and 28 days thereafter. At the same time points, haemostatic system activation was investigated by measuring prothrombin fragment f1.2 (f1.2) and thrombin antithrombin complexes (TAT) in venous blood and in blood emerging from a skin incision (shed blood).The mean FVIII level before propranolol was 192 IU/dL and 115 IU/dL in patients with high and low FVIII, respectively. During and 28 days after propranolol, no significant change in FVIII was seen in both groups. Changes in f1.2 and TAT were not detectable in either venous blood or in shed blood.β-receptor blockade did not lower FVIII or inhibit haemostatic system activation in patients with VTE and persistently high FVIII. Administration of propranolol cannot be recommended as secondary thromboprophylaxis in patients with high FVIII.
Keywords: Venous thrombosis; factor VIII; ß-receptor blockade; thrombin generation